(untitled) (Research, Society and Development, 2021)
Pressure injury (LP) occurs when a tissue is compressed by a bone prominence in contact with a surface. Their presence may aggravate the patient’s state of health, generating pain and systemic impairment. The high rates of incidence, prevalence, mortality and costs from this condition, represent a serious public health problem. This study aimed to know the clinical and epidemiological profile of patients who acquired the LP during the hospitalization period, comparing the characteristics between the public and private hospitals. This is an analytical, comparative study with a quantitative approach, carried out by analyzing medical records, of adult patients who acquired LP during hospitalization in public and private hospitals. The general clinical profile of patients who acquired pressure injury in the hospital setting was: 50% female and 50% male; elderly (62%); with short hospital stay <1 month (64%), who received multidisciplinary care (97%) and physiotherapy (86%) and died (68%). The socio-demographic and clinical reality of the patients who acquired LP in both hospitals were similar, which shows that the risk factors are not related to the type of public or private assistance, except in relation to the age group and associated disease. We emphasize the high incidence of death found in the studied population, which demonstrates the necessity to extend the preventive.